2015
DOI: 10.1177/1056789515615184
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sea and distilled water conditioning on the overall mechanical properties of carbon nanotube/epoxy composites

Abstract: The study of mechanical properties of carbon nanotube reinforced polymeric materials under different environmental conditions are very much essential as this material possesses potential for using it in structural parts, automobiles, marine field and so on. This study deals with the effect of moisture absorption on the mechanical and thermal properties of carbon nanotube/epoxy composites by immersing it in sea and distilled water at 30℃ temperature and at 75% Relative Humidity (RH) humidity. Composite specimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 28 publications
4
22
0
Order By: Relevance
“…Figure 1 shows the water uptake in terms of percentage of the initial weight for the in-bulk cured samples at each condition. The graph is in good agreement with the typical behavior of water uptake for this kind of samples, previously stated in other studies [38,41,42]. It is observed that water uptake is more prevalent in the initial stages and then the weight gain is going less significant until the water saturation is reached at 2 weeks of aging.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Figure 1 shows the water uptake in terms of percentage of the initial weight for the in-bulk cured samples at each condition. The graph is in good agreement with the typical behavior of water uptake for this kind of samples, previously stated in other studies [38,41,42]. It is observed that water uptake is more prevalent in the initial stages and then the weight gain is going less significant until the water saturation is reached at 2 weeks of aging.…”
Section: Resultssupporting
confidence: 91%
“…The water uptake generally induces the creation of weak hydrogen bonds, leading to a swelling of the polymer chains and causing, thus, a drastic reduction of the physical properties. This effect is called plasticization and is detrimental to the mechanical properties [41]. However, after this initial stage, a slight recovery is generally observed.…”
Section: Electrical Monitoringmentioning
confidence: 99%
“…Similar exotherms corresponding to unreacted epoxy were observed in cycle 1 for all the exposed specimens (Fig. S9), which suggests the absence of additional secondary cross-linking reactions between water and unreacted epoxides, often observed during long term hydrothermal experiments [43], [46]. …”
Section: Resultssupporting
confidence: 73%
“…Besides, hygroscopic stress at the CNT/epoxy interface due to the higher affinity of epoxy toward water due to the presence of OH group, than CNTs, could also generate microscopic debonded zones. [ 30,52 ] These micro‐cracks act as a new possible route for accelerated water absorption due to their capillary action.…”
Section: Resultsmentioning
confidence: 99%